I FELT GUILTY [THAT] I DIDN’T DO ENOUGH. ORGANIZATIONAL AND POLICY RESPONSES EXACERBATED FRONTLINE SOCIAL WORKER DISTRESS - Teixeira, Katja; Opolko, Christina; Sussman, Tamara (Canadian Social Work Review / Revue canadienne de service social, 2022)
This study explores urban social workers’ experiences working the front lines during COVID-19’s first wave. It aims to uncover social workers’ shifts in roles and responsibilities across the health and social service network, to illuminate how these shifts impacted them, and ultimately to derive meaning from these experiences to inform future directions for the profession. Eight social workers from a range of contexts were interviewed. Our analyses revealed that, while all participants described some negatives of front-line pandemic work, the frequency and intensity of these moments were exacerbated by organizational and policy responses. When social workers were expected to work outside of their scope of practice, when their skills were overlooked or underutilized, and when their organizational contexts focused on individual distress rather than collective support, they reported intensified periods of distress. If we hope to retain the health and wellbeing of our workforce and preserve the value of the profession, systemic preventative responses must take priority. Building opportunities for collective on-going peer support and debriefing, leveraging the expertise of social workers to address psychosocial issues, and including the voices of front-line workers in the development of solutions to pandemic-related hardships may help reduce social work distress and improve front-line workers’ responses to social issues.